Pengembangan Multimedia Video Tutorial Penataan Rambut Gala style dengan Teknik Kepang - Aisyah Fourindha; Tresna Prihatin, Pipin; Wibawa Sakti, Asri (Jurnal Tata Rias, 2024)
Hair styling is all stages starting from washing, styling to beautifying the shape of the hair. The aim of this research is to identify the use of media in hair styling material in the Hair Beauty and Beauty course, design and create multimedia video tutorials on gala style hair styling using braid techniques, validate with material experts and multimedia experts and user trials and carry out analysis and revision to find out multimedia feasibility. The method used in this research is the Research and Development (R&D) method which is used to produce products and test the effectiveness of these products. The procedure for developing multimedia video tutorials goes through: (1) Identification Phase, (2) Planning Phase, (3) Creation Phase, (4) Validation Phase, (5) Revision Phase, (6) User testing phase. The results of multimedia video tutorial validation by material experts obtained an average percentage value of 92.1%. The results of multimedia expert validation obtained an average percentage value of 92%. The results of user trials obtained an average percentage value of 88.6%. The findings in this research indicate that the multimedia video tutorial on gala style hair styling using the braiding technique is in the very good category and is very suitable for use as learning multimedia because it only requires slight improvements to the multimedia video tutorial that has been made and the material that has been presented.